Preliminary study evaluating the assessment of changes in pulmonary function associated with body positioning in dogs with suspected aspiration pneumonia. Issue 1 (20th December 2022) - Ten Cate, Soscha C.; Urion, Rebecca; Hostnik, Eric T.; Yaxley, Page E.; Cooper, Edward S.
Abstract: Objective: To evaluate the variability in arterial blood gas (ABG) assessment of pulmonary function with different body positioning in dogs with suspected aspiration pneumonia. Key Findings: The median differences in alveolar–arterial gradient, Pao 2, and Paco 2 values in different recumbencies were not statistically significantly different, both within patients and across the study population. No difference was noted in ABG values in the subgroups with unilateral or bilateral disease or that were more affected on the right side versus the left side. Significance: This preliminary study provides data that can be used to calculate appropriate sample sizes for subsequent studies investigating the impact of recumbency on pulmonary function in patients with aspiration pneumonia.